KVK interventions in yield and economics of groundnut cultivation in chengalpattu district - Gayathri Subbiah, (Annals of Agricultural Research, 2024)
The study on Integrated Crop Management practices in Groundnut cultivation was carried out from 2020 21 to 2022-23 in Chengalpattu district of Tamil Nadu with the scope of demonstrating the recent technolo gies in Groundnut and its attributes on yield and economics of the crop. Training, Field visits, and Cluster Frontline demonstrations were conducted by KVK. Demonstrations in Groundnut cultivation technologies were carried out in an area of 40 ha. The technologies recommended for adoption included the cultivation of recently released varieties, seed treatment with bio agents, balanced and recommended fertilizer applica tion, and integrated pest management. Critical inputs like seeds, bioagents, and crop boosters along with traps were distributed to the farmers. Demonstrated areas recorded increased yield compared to farmer’s fields. The yield obtained in demonstrated fields were 32.56 q/ha (Kadiri 1812), 36.05 q/ha (Dharani TCGS 1043), and 21.00 q/ha (VRI 8) compared to the farmer’s practice of cultivating G 7 and G 9 varieties. The root rot disease incidence was not reported in Kadiri 1812 with least in Dharani TCGS 1043 fields (2 %). Tobacco cutworm infestations were not observed in Kadiri 1812 and in Dharani TCGS 1043 and VRI 8 fields, it was reported as 2.6% and 3% compared to farmer’s check plots. BCR ratios were 3.91 (Kadiri 1812), 2.09 (Dharani TCGS 1043) and 1.75 (VRI 8) respectively.